2020
DOI: 10.1016/j.psj.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the physical meat quality in partridge (Alectoris chukar) and its relationship with intramuscular fat

Abstract: This study was undertaken to assess the effect of various levels of intramuscular fat ( IMF : <0.5%, 0.5–0.99%, 1.0–1.49%, 1.5–1.99%, 2.0–2.49%, and >2.5%) on the physical meat quality of partridge. Physical characteristics such as moisture, pH, shear force, water-holding capacity ( WHC ), and color, along with IMF, were measured on 414 partridges (pectoral muscle). In this study, partridge meat was described as a kind of tender and moderately juicy meat with a nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Their detailed information on carcass and meat quality traits between the two groups was presented in Table 1 and Supplementary Table S1. In comparison with the L-WHC group, the H-WHC group showed lower 35kg Water loss (%) (p < 0.05) of LD muscle, demonstrating WHC had a significantly negative correlation with water loss, which was consistent with previous studies 5,15,16 .…”
Section: Phenotypic Information Of Chinese Simmental Beef Cattlesupporting
confidence: 90%
See 2 more Smart Citations
“…Their detailed information on carcass and meat quality traits between the two groups was presented in Table 1 and Supplementary Table S1. In comparison with the L-WHC group, the H-WHC group showed lower 35kg Water loss (%) (p < 0.05) of LD muscle, demonstrating WHC had a significantly negative correlation with water loss, which was consistent with previous studies 5,15,16 .…”
Section: Phenotypic Information Of Chinese Simmental Beef Cattlesupporting
confidence: 90%
“…Farouk et al found WHC was higher in Bovine M. semimembranosus with inherently higher pH compared to lower pH 19 . Conversely, Wen et al revealed WHC had significant and negative genetic correlations with pH 16 . The reason for the opposite conclusions of the above studies on the correlation between WHC and pH was that WHC was measured at different periods after animal slaughter.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, pH had a significant correlation with IMF, but not with WHC, which was consistent with the correlation between pH and IMF reported in the previous study 27 . WHC increased linearly as pH increased in the LD muscle of beef 31 , inversely, it was negatively correlated with pH in pork and partridge 14 , 32 . The relationship between pH and WHC was not consistent among studies, including our own.…”
Section: Discussionmentioning
confidence: 92%
“…Farouk et al found WHC was higher in Bovine M. semimembranosus with inherently higher pH compared to lower pH 17 . Conversely, Wen et al revealed WHC had significant and negative genetic correlations with pH 14 . The reason for the opposite conclusions of the above studies on the correlation between WHC and pH was that WHC was measured at different periods after animal slaughter.…”
Section: Introductionmentioning
confidence: 93%